2019
DOI: 10.1002/jcp.29102
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Kank1 expression regulates YAP to promote apoptosis and inhibit proliferation in OSCC

Abstract: The kidney ankyrin repeat-containing protein 1 (Kank1) gene is one of the most important members of the KANK family. Kank1 has hybridity deletion and promoter methylation in the cancer tissues of the brain, lung, kidney and the corresponding cell lines, leading to downregulation of the gene expression. Meanwhile, Kank1 also plays a key role in the occurrence and development of various types of tumors, suggesting that Kank1 may be an anti-oncogene. However, its role and the potential mechanisms in the Oral Squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The humanized mouse, which is developed by transplanting functional human cells or tissues into immunodeficient Il2rg null mice, is an emerging preclinical model for studying human disease (160). For the study of tumors, current research focuses on [1] the establishment of novel tumor models (such as humanized CDX tumor models and humanized PDX tumor models) that are associated with human tumor-immune system interactions and [2] the exploration of therapy (including NK cell therapy, T cell editing, cytokine therapy, co-stimulatory enhancement, and checkpoint inhibitors) (161).…”
Section: Humanized Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The humanized mouse, which is developed by transplanting functional human cells or tissues into immunodeficient Il2rg null mice, is an emerging preclinical model for studying human disease (160). For the study of tumors, current research focuses on [1] the establishment of novel tumor models (such as humanized CDX tumor models and humanized PDX tumor models) that are associated with human tumor-immune system interactions and [2] the exploration of therapy (including NK cell therapy, T cell editing, cytokine therapy, co-stimulatory enhancement, and checkpoint inhibitors) (161).…”
Section: Humanized Mouse Modelsmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is one of the most common human malignancies and endangers human health, and it accounts for 40% of all head and neck squamous cell carcinoma (HNSCC) cases (1,2). Although cancer treatments have developed rapidly, the 5-year survival rate for OSCC is still only remained at 50% over the last few decades (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…33 Fan et al validated KANK1 as a dysregulated gene in OSCC, which modulates proliferation and apoptosis through YAP. 28 There was also evidence exhibited that elevating KANK1 expression suppressed lung cancer progression by regulating invasion, migration and apoptosis of tumor cells. 34 Consistent with our study, Chen and colleagues documented that the expression of KANK1 was decreased and associated with the growth and apoptosis of GC tumor both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…27 Research workers also found that KANK1 had a poor expression in oral squamous cell carcinoma, and overexpression of KANK1 inhibited the proliferation and elevated the apoptosis rate of tumor cells. 28 Besides, the Wnt/β-catenin signaling was known as an important pathway which regulated many cellular progresses in human body, and the aberrant modulation of Wnt/β-catenin pathway had been validated in GC. 29 Xu et al proposed that blocking the Wnt/β-catenin signaling could effectively inhibit the proliferation, EMT and chemo-resistance of GC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Non-protein-coding sequences of the human genome account for over 70% of the noncoding RNAs (ncRNAs) (1)(2)(3). Recent studies have shown that ncRNAs act as a necessary element in many kinds of biological processes, including post-transcriptional regulation, epigenetics, chromatin modification, and the cell cycle (4,5). It is increasingly being reported that ncRNAs also affect human cancers and disease progression (6).…”
Section: Introductionmentioning
confidence: 99%